Europäischer Buchmarkt und Gelehrtenrepublik Die transnationale Verlagsbuchhandlung Treuttel & Würtz, 1750-1850 - Haß, Annika (Pariser Historische Studien, 2023)
The publishing house and bookshop Treuttel & Würtz was a hub of European exchange par excellence around 1800. While the publishing house targeted a transcultural elite audience with publications by Johann Wolfgang von Goethe or Germaine de Staël, the bookshop supplied customers throughout Europe with its branches in Strasbourg, Paris and London as well as its widely ramified trade network. For the first time, this study examines the working and influence of the publishing bookshop and embeds it in the cultural-historical context: from the organisation of the book trade and the cooperation between booksellers to library history and the emergence of new academic disciplines such as the modern philologies at the beginning of the 19th century. All these areas were characterised by a transnational market, which was served by Treuttel & Würtz in a way that can be described as practised world literature.